6(10-3x)=-12

Simple and best practice solution for 6(10-3x)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(10-3x)=-12 equation:


Simplifying
6(10 + -3x) = -12
(10 * 6 + -3x * 6) = -12
(60 + -18x) = -12

Solving
60 + -18x = -12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-60' to each side of the equation.
60 + -60 + -18x = -12 + -60

Combine like terms: 60 + -60 = 0
0 + -18x = -12 + -60
-18x = -12 + -60

Combine like terms: -12 + -60 = -72
-18x = -72

Divide each side by '-18'.
x = 4

Simplifying
x = 4

See similar equations:

| 82x^2+18x+1= | | 8x^3+5x^2+40x+25=0 | | 17x-2(x-7)=14-5x | | 21=x^18 | | 4w^2+36w+81= | | 10k^2-37k+7=0 | | -4(6x+5)=-44 | | 1.25x+.85y=9.25 | | 31+(27+X)=150 | | 8(x+3)=5x+8+7x | | 5f+4-3f=20 | | 4(x-4+4)-10x=30 | | (14x+10)+(16x-4)=180 | | 24u^4w^5x^7-20u^6w^9= | | 20=1 | | 4x-4+4-10x=30 | | 30u^2w^5+5u^8w^4y^9= | | 0=.088x^2+2.5x | | 40-8x=-56-12x | | -3(3+5x)=-144 | | 2(x+3)-8x=42 | | nx-r=pforx | | 3(x+3)+2x=29 | | -3(3+5x)=-112 | | 18uv^2w^3+30u^6v^5= | | -6(5+x)=24 | | 3y-6+y+40=8y+40-6y | | No-r=p | | 4(5-x)(x+6)=0 | | 0P=30 | | 6x-(5-4x)=5 | | (x^2-6x+5)(7x-4)= |

Equations solver categories